Development of Student Performance Character Education Models - Dodi Ahmad Haerudin; Cece Rahmat; Encep Syarief Nurdin; Abdul Somad (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to develop a model of performance character education, find out the performance character education model applied to middle schools, and determine the inhibiting factors to the effectiveness of the character education model applied in middle schools. Also, it aims to know the hypothetical model of performance character education. The method used in this research was research development or research development (R&D) from Borg & Gnall. The subject of this research was SMA/MA Kuningan which was determined by purposive sampling of 120 students. The development stages included information gathering research, planning, initial model design, preliminary testing & model revision, main model testing & model revision II, operational testing & model revision III, and performance character education models. The results of this study indicated that the performance character education model effectively strengthened the performance character of students at school. The inhibiting factors for character building are lack of student awareness, family factors, unsupportive society, misused technological developments, and character education models that have proven to influence student performance character positively and effectively.